Covalently linking CuInS2 quantum dots with a Re catalyst by click reaction for photocatalytic CO2 reduction. Issue 31 (18th July 2018) - Huang, Jing; Gatty, Mélina Gilbert; Xu, Bo; Pati, Palas Baran; Etman, Ahmed S.; Tian, Lei; Sun, Junliang; Hammarström, Leif; Tian, Haining
Abstract : Covalently linking a Re catalyst to CuInS2 QDs through a facile click reaction for efficient electron transfer to improve photocatalytic CO2 reduction is reported. Abstract : Covalently linking photosensitizers and catalysts in an inorganic–organic hybrid photocatalytic system is beneficial for efficient electron transfer between these components. However, general and straightforward methods to covalently attach molecular catalysts on the surface of inorganic semiconductors are rare. In this work, a classic rhenium bipyridine complex (Re catalyst) has been successfully covalently linked to the low toxicity CuInS2 quantum dots (QDs) by click reaction for photocatalytic CO2 reduction. Covalent bonding between the CuInS2 QDs and the Re catalyst in the QD–Re hybrid system is confirmed by UV-visible absorption spectroscopy, Fourier-transform infrared spectroscopy and energy-dispersive X-ray measurements. Time-correlated single photon counting and ultrafast time-resolved infrared spectroscopy provide evidence for rapid photo-induced electron transfer from the QDs to the Re catalyst. Upon photo-excitation of the QDs, the singly reduced Re catalyst is formed within 300 fs. Notably, the amount of reduced Re in the linked hybrid system is more than that in a sample where the QDs and the Re catalyst are simply mixed, suggesting that the covalent linkage between the CuInS2 QDs and the Re catalyst indeed facilitates electron transfer from the QDs to the Re catalyst. Such an ultrafast electron transfer in the covalently linked CuInS2 QD–Re hybrid system leads to enhanced photocatalytic activity for CO2 reduction, as compared to the conventional mixture of the QDs and the Re catalyst.